Universal Basic Income: Malaysia's Golden Opportunity to Lead an Islamic Economic Revolution - Irma Naddiya Binti Mushaddik; Abdulwahed Jalal Nuri; Zhilwan Tahir (Penerbit Hellow Pustaka, 2025)
As the global economy grapples with rising inequality, technological disruption, and the socio-economic aftermath of the COVID-19 pandemic. Universal Basic Income (UBI) has gained traction as a promising policy to promote economic security and social justice. This article examines UBI using a qualitative, conceptual, and normative approach, analysing its compatibility with key principles of Islamic economics, such as Zakat (mandatory almsgiving), Sadaqah (voluntary charity), Maslahah(public interest), and I’tidal (balance and moderation). By drawing on Islamic teachings, classical scholarship, and modern economic thought, the article argues that UBI aligns closely with Islamic ethical values and offers a practical, morally sound solution to addressing poverty and inequality. The paper further suggests that Malaysia, with its strong Islamic finance sector and advanced digital infrastructure, is well-positioned to pioneer the global rollout of UBI. Through descriptive and critical analysis and secondary data, it explores how Islamic financial tools like Waqf, Sukuk, and a reformed Zakat system could sustainably fund UBI. In doing so, Malaysia has the opportunity to lead in developing a transformative economic model inspired by Islamic principles.